Market access : unfinished business : post-Uruguay Round inventory and issues (WTO GenevaCH, 2001)
Seeks to evaluate post-Uruguay Round market access conditions, and to contribute to a clarification of the stakes in the ongoing process of multilateral trade negotiations in the market access area. Provides a brief overview of the progress to date in the mandated negotiations on agriculture and services.
Bibliography: p. 141